2017
DOI: 10.14740/jocmr2976w
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of SGLT2 Inhibitors in Reducing Glycated Hemoglobin and Weight in Emirati Patients With Type 2 Diabetes

Abstract: BackgroundSGLT2 inhibitors are a new class of drugs that act by inhibiting glucose reabsorption in the proximal renal tubules. Many trials have demonstrated their effectiveness in reducing glycated hemoglobin (HbA1c) and weight, but they have never been examined in Arab or Emirati populations.MethodsWe assessed the efficacy of SGLT2 inhibitors in reducing HbA1c and weight in our population and specifically in an Emirati cohort. We also assessed the effect on fasting blood glucose, blood pressure, lipid profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Adding SGLT2 inhibitors in patients receiving first‐line monotherapy resulted in an increase proportion of subjects achieving a HbA1c <7%, with low risk of hypoglycaemic events . In addition to glycaemic control, SGLT2 inhibitors cause a weight reduction of approximately 2 kg already at 6 weeks after initiation of therapy . The most common adverse events include urinary tract infections and vulvovaginitis/balanitis with higher incidence in female than male, which could be linked to an increase urinary glucose excretion and which may limit utilization of this drug in immunocompromised patients …”
Section: Glycosuricsmentioning
confidence: 99%
“…Adding SGLT2 inhibitors in patients receiving first‐line monotherapy resulted in an increase proportion of subjects achieving a HbA1c <7%, with low risk of hypoglycaemic events . In addition to glycaemic control, SGLT2 inhibitors cause a weight reduction of approximately 2 kg already at 6 weeks after initiation of therapy . The most common adverse events include urinary tract infections and vulvovaginitis/balanitis with higher incidence in female than male, which could be linked to an increase urinary glucose excretion and which may limit utilization of this drug in immunocompromised patients …”
Section: Glycosuricsmentioning
confidence: 99%
“…Likely, the bodyweight also reduced from the baseline at the sixth month, from 85.7±17.8 kg to 84±12.2 kg (p=0.0001). (Bashier et al, 2017)…”
Section: Effects Of Sglt-2 Inhibitorsmentioning
confidence: 99%
“…Consequently, SGLT2 inhibitors reduce plasma glucose in an insulin-independent manner and improve insulin resistance in diabetes [22]. SGLT2 inhibitors were shown to reduce glycated haemoglobin (HbA1c) by approximately 0.6%–1.2%, with a lower rate of hypoglycaemia [23]. Four recent major trials have shown that SGLT2 inhibitors are superior to other anti-diabetic medications in the prevention of cardiovascular events and renal protection [5,24,25,26].…”
Section: Reno-cardiovascular Protection Of Sglt2 Inhibitionmentioning
confidence: 99%